Pengaruh Pemanfaatan Teknologi Informasi Terhadap Pengembangan UMKM Fashion di Era Digital - Sari, Kartika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of the use of information technology on the development of fashion MSMEs in the digital era. The research method used is explanatory research. The population of the study was 32 fashion MSME actors. The sampling technique was purposive sampling and used a Linear Regression statistical test tool, with independent variables of the use of information technology and the use of information technology, and the dependent variable of fashion MSMEs. The results of this study are that the use of information technology and the use of information technology partially have a significant effect on the development of fashion MSMEs in the digital era.